Understanding Nitrilotris(methylenephosphonic acid) reactions with ferric hydroxide. (May 2017) - Martínez, Rodrigo Javier; Farrell, James
Abstract: Phosphonate compounds are used in a wide variety of industrial and agricultural applications, and are commonly found in surface and ground waters. Adsorption to ferric hydroxide can have a significant effect on the transport and fate of phosphonate compounds in the environment. This research used density functional theory modeling to investigate the adsorption mechanisms of nitrilotris(methylenephosphonic acid) (NTMP) on ferric hydroxide. Standard Gibbs free energies of reaction ( Δ G r o ) and reaction activation barriers (Ea ) were calculated for different possible adsorption mechanisms. Physical adsorption of NTMP to ferric hydroxide was promoted by negative charge assisted hydrogen bonding, and had Δ G r o ranging from −2.7 to −7.4 kcal/mol. NTMP was found to form three different types of inner sphere complexes, monodentate, bidentate mononuclear and bidentate binuclear. For the monodentate complexes, Δ G r o ranged from −8.0 to −13.7 kcal/mol, for the bidentate complexes Δ G r o ranged from −15.3 to −28.9 kcal/mol. Complexation with Ca 2+ decreased the energy for physical adsorption but increased the binding energies for mono- and bidentate complexes. Complexation with Ca 2+ also allowed formation of a tridentate ternary surface complex, whereby the Ca 2+ ion formed a bridge between three FeO − and three PO − groups. Physical adsorption had Ea = 0, but mono- and bidentate complex formation had Ea values ranging from 36 to 53 kcal/mol. Formation of tridentate ternary surface complexes involving Ca 2+ had the lowest activation barriers of 8 and 10 kcal/mol. The different activation barriers for different modes of adsorption may explain previous experimental observations of unusual kinetic behavior for adsorption and desorption of NTMP. Graphical abstract: Highlights: Adsorption of NTMP on ferric hydroxide occurs via physical and chemical adsorption. Physical adsorption was promoted by negative charge assisted hydrogen bonding. Four types of chemical adsorption complexes were identified. Inner-sphere complex formation had high activation barriers. Ca 2+ ions promoted the formation of ternary complexes with lower activation barriers.